2001
DOI: 10.1067/mva.2001.112319
|View full text |Cite
|
Sign up to set email alerts
|

Extra-anatomic arterial reconstruction with ligation of common iliac arteries and embolization of the aneurysm for the treatment of abdominal aortic aneurysms in high-risk patients

Abstract: Combining an extra-anatomic bypass graft and complete exclusion of the AAA by ligation of the common iliac arteries and a coil embolization is an effective, less invasive treatment option for patients with AAA and prohibitive operative risk. We emphasize the need for complete embolization documented by decreased aneurysm size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In exclusion of The survival rate is 66.7% at three years and 41.7% at five years abdominal aortic aneurysms, Resnikoff reported that 14 (1.7%) of 831 patients required surgical intervention [11]. Huber described that complete thrombosis of abdominal aortic aneurysm, which was not accomplished without exclusion, prevented future rupture [12]. We think that complete thrombosis by exclusion minimizes the risk of rupture of IIAA in the long-term period.…”
Section: Discussionmentioning
confidence: 97%
“…In exclusion of The survival rate is 66.7% at three years and 41.7% at five years abdominal aortic aneurysms, Resnikoff reported that 14 (1.7%) of 831 patients required surgical intervention [11]. Huber described that complete thrombosis of abdominal aortic aneurysm, which was not accomplished without exclusion, prevented future rupture [12]. We think that complete thrombosis by exclusion minimizes the risk of rupture of IIAA in the long-term period.…”
Section: Discussionmentioning
confidence: 97%
“…Extra-anatomic bypass grafts such as axillofemoral and subclavio-femoral femoro-femoral can be applied in the patients having the infected aortic grafts, in the patients undergoing colostomy and ileostomy after the previous laparotomy, having acute myocardial infarction, severe congestive heart failure, severe chronic renal disease or renal failure requiring hemodialysis, malignancy, resting dyspnea, patients with chronic obstructive pulmonary disease (COPD) [8,9]. Axillo-femoral bypass grafting may be preferred instead of femoro-femoral bypass in patients with operation-related graft infections [10].…”
Section: Discussionmentioning
confidence: 99%
“…Axillofemoral bypass was applied to patients with an ankle-brachial index greater than one. Femoro-femoral (FF) bypass can be preferred in cases where anatomic bypass cannot be performed due to an extremely plaque with unilateral iliofemoral obstruction and is also at high risk, and if the contralateral femoral artery flow is angiographic and hemodynamically sufficient [9,10]. It has been reported that the 5-year patency rate is significantly reduced if there is an obstruction in the superficial femoral artery [11].…”
Section: Discussionmentioning
confidence: 99%
“…6 In this series, occlusion was achieved in 12 of 15 patients, with the three failures requiring intravascular occlusion using bucrylate. Numerous case series have been published, [5][6][7][8][9][10][11][12][13][14] ranging from 4 to 60 patients, on outcomes of extra-anatomic bypass, followed by aortic occlusion. All patients had contraindications to open aortic aneurysmorrhaphy.…”
Section: Discussionmentioning
confidence: 99%